Impaired Recall of CD8 Memory T Cells in Immunologically Privileged Tissue - Dai, Zhenhua; Nasr, Isam W; Reel, Michael; Deng, Songyan; Diggs, Lonnette; Larsen, Christian P; Rothstein, David M; Lakkis, Fadi G (The Journal of immunology (1950), 2005)
Foreign Ags that enter immunologically privileged sites such as the eye, brain, and testis persist for an extended period of time, whereas the same Ags are rapidly eliminated at conventional sites. Immune privilege, therefore, provides unwanted refuge for pathogens and tumor cells but is beneficial for the survival of allogeneic grafts. In this study, we asked whether memory T cells can eliminate foreign Ags deposited at an immunologically privileged site by studying CD8 memory T cell-mediated rejection of pancreatic islet allografts placed either in the testis (a privileged organ) or under the kidney capsule (a nonprivileged site) of diabetic mice. We found that CD8 memory T cells reject intratesticular grafts at a significantly slower rate than the rejection of intrarenal grafts. Delayed graft rejection in the testis was not due to reduced homing or proliferation of memory T cells but due to their increased apoptosis at that site. Apoptosis was mediated by the combined actions of two TNFR family members that are up-regulated on activated memory T cells, Fas, and CD30. Therefore, memory T cells survey immunologically privileged tissues but are subject to the immunosuppressive mechanisms present at these sites.